Assessing Resistance of the Microbial Community in Soils to Pollution with Antibiotics - Akimenko, Yuliya Viktorovna (Asian Journal of Pharmaceutics (AJP), 2018)
Objective: The study is aimed at assessing resistance of the microbial community in soils (on the example of typical chernozem) to contamination with antibiotics of various chemical nature and spectra of activity (benzylpenicillin, ampicillin, streptomycin, oxytetracycline, tylosin, farmasinum, tromexin, aliseryl, nystatin, and input). Methods: The comprehensive study of microbiocenosis in soil included determination of the total number of bacteria by the method of fluorescent microscopy with staining of the samples with acridine orange, determination of the abundance of viable microorganisms of various ecological trophic groups with the use of the methods of sowing on solid nutrient substrate. Reaction of the substrate (pH) was determined by the potentiometric method in soil suspension 1:2.5. Results: The research has shown that chernozem contamination with antibiotics reduces the total number of bacteria, decreasing the number of individual ecological trophic groups of microorganisms, and changes their ratio. Contamination with antibiotics results in significant reduction in the number of ammonifying bacteria, which are represented most widely of the various ecological trophic groups of soil microorganisms. Most studied microbiological parameters get reduced when the concentration of antibiotics reaches 100 mg/kg of soil. The maximum influence of antibiotics is noticed within the first 10 days from the moment of contamination. The degree of antibiotics influence is determined by their nature, concentration, and time of exposure. Antibacterial antibiotics have a more inhibitory action on the microbial community, compared to the fungicidal ones. The effect of antibiotics on soil microbial coenosis has prolonged nature. Conclusions: By the degree of soil inhibition with microorganisms, antibiotics form the following line: Ampicillin > benzylpenicillin â‰¥ streptomycin > tylosin â‰¥ farmasinum > nystatin > tromexin > aliseryl. The degree of resistance to antibiotics, the studied microorganisms of chernozem formed the following line: Bacteria g. Azotobacter > micromycetes > amylolytic bacteria > ammonifying bacteria. The number of ammonifying bacteria is the most informative microbiological indicator of contamination with antibiotics. The indicator of g. Azotobacter bacteria abundance is uninformative in case of contamination with antibiotics.